ERCP procedures as a source of radiation risk to a single gastroenterologist - Maria A. Staniszewska; Krzysztof Kujawski; Renata Kopeć; Krzysztof Sasak (Nofer Institute of Occupational Medicine, 2017)
Background: One of the numerous sub-areas of interventional radiology is the use of X-rays in gastroenterology. X-ray fluoroscopy is applied in therapeutic procedures, including endoscopic retrograde cholangiopancreatography (ERCP) that is frequently performed. The ERCP procedure is aimed at imaging the pancreatic duct and biliary tracts. Material and Methods: In this paper radiation risk to the gastrenterologist performing ERCP procedures was investigated. The procedures were performed by a single gastroenterologist in the ERCP Laboratory, University Clinical Hospital Military Memorial Medical Academy - Central Veterans' Hospital in Łódź, Poland. The study comprised 2 series of measurements, one taken during the procedures with continuous fluoroscopy mode, the other during procedures with fluoroscopy in pulsed mode at a frequency of 3 pulses/s. Exposure parameters, anatomical data of patient and dose equivalents for the eyes, skin of the hand and the effective dose for whole body of the gastroenterologist were recorded during each procedure. Results: The collected data cover 70 ERCP procedures - 40 procedures were controlled by continuous fluoroscopy and 30 by pulsed fluoroscopy. The results reveal that pulsed fluoroscopy makes it possible to reduce doses received by the gastroeneterologist from 45% to 60% compared to continuous fluoroscopy. Conclusions: Endoscopic retrograde cholangiopancreatography procedures can cause radiation risk to the gastroenterologist performing them. The use of continuous fluoroscopy can result in achieving an equivalent dose to eye lens nearly 20 mSv per year, i.e., the decreased annual limit recommended by the International Commission on Radiological Protection (ICRP). Med Pr 2017;68(6):735-741